Pembuatan Game dengan Menerapkan Metode Decision Tree: UCB1, untuk Menentukan Pemilihan Strategy dalam AI. - Erick Santoso; Gregorius Satia Budhi; Rolly Intan (Jurnal Infra, 2017)
So that the aim of this research is to testing how good is UCB1 method when implemented into the main method that the game works.The test will test the UCB1 method work as the movement of enemy diffilcuty level. But with some rules that make this method become more flexible to use. So the enemy diffilcuty will adapt to player diffilcuties.The result of this research is the UCB1 method can be use to enemy diffilcuty level movement. This method can make the enemy become more adapt to the player.